Peran Edukasi Pertanian berbasis Teknologi dalam Meningkatkan Minat Generasi Z terhadap Pertanian Modern (Modern Farming) - Abdan, Muh. (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2025)
Indonesia is a country with enormous opportunities in the agricultural sector, but its people's interest in working in the sector is low. This study aims to determine Generation Z's perception of technology-based agricultural technology education and to determine the role of technology in agriculture influencing Generation Z's interest in pursuing a profession as a farmer. The research method uses a qualitative descriptive approach with interviews with 12 informants, consisting of 6 main informants and 6 additional informants. The findings show that the use of augmented reality technology as an educational medium received a positive response from informants. Interactive visualizations, 3D images, and interesting learning experiences are considered very helpful in increasing understanding of the modern agricultural technology that is conveyed. After education based on augmented reality technology, there was a change in informants' interest in agriculture which was marked by an interest in re-engaging in similar activities and a desire to further explore the agricultural sector.